Brain Dominance Using Brainwave Signal - Mahfuzah, Mustafa; Nur Syuhaida Hani, Abdul Hamid; Nor Rul Hasma, Abdullah; Rosdiyana, Samad; Pebrianti, Dwi (IEEE, 2015)
The study of brain dominance in human-computer interaction has increased in recent years in an attempt to address the need of users especially who cannot read or write. The objective of this paper is to determine the brain dominance from brainwave signal that are measured using Emotive device and to analyse the pattern of brain dominance brainwave signal by using signal processing. The result of Power Spectral Density (PSD) and Energy Spectral Density (ESD) from brainwave will be validated with Hermann Brain Dominance Instrumentation (HBDI) questionnaire. The result shows that most sample are left brain dominance. The result also shows that Beta and Delta indicate the left-brain dominance whereas Beta is indicates rightbrain dominance.